(untitled) (Revista Cerrados, 2010)
Destino e heroísmo no teatro épico brechtiano Por meio da análise de personagens de textos dramáticos de Brecht, dentre as quais tomo Antígona como ponto de partida, procuro discutir como os conceitos de destino e heroísmo são reconfigurados pelo teatro épico brechtiano. Palavras-chave: destino; heroísmo; teatro épico; Bertolt Brecht. Fate and heroism in the Brechtian theater epic Through the analysis of characters in dramatic texts by Brecht, among which Antigone is taken as a starting point, my purpose is to discuss how the concepts of fate and heroism are reconfigured by the Brechtian epic theater. Keywords: fate; heroism; epic theater; Bertolt Brecht.